HUFFMAN COMPRESSION ALGORITHM - Kairišs, Edgars; Kijaško, Mihails (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
In modern IT world, we are returning to the problem of low storage space. May be typically users do not see this problem and still there is more data that companies collect and should store. In this work author analyzed Huffman compression algorithm it’s effectiveness, working principles and examples of usage.